Investigation of Musculoskeletal Symptoms (MSS) and Manual Handling Risk Factors (MHRFS) among Students at School - Ridhwan, Nurul Atiqah; Mohd Nasrull Abdol Rahman, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The study aims to investigate musculoskeletal symptoms (MSS)among primary and secondary school students using the BodySymptoms Survey (BSS), assess manual handling risk factors (MHRFs)with the Manual Handling Assessment Charts (MAC), and recommendimprovements for student manual handling practices, focusing onheavy school bags, improper carrying techniques, and ergonomicdeficiencies.The study employed a mixed-methods approach with 130volunteer primary and secondary school students in Parit Raja.focusing on musculoskeletal symptoms. Quantitative data, includingmean, mode, median, and standard deviation, were analyzed usingdescriptive statistics. The Body Symptoms Survey and ManualHandling Risk Assessment were integrated to assess and correlatemanual handling risk factors impacting student health. The manualhandling risk assessment of 130 students identified varying risk levelsfrom carrying heavy school bags. Most students scored low (0-4),indicating no immediate action required. However, a notable portionscored moderate to high (5-16), highlighting the need for promptinterventions to mitigate risks and ensure student safety, particularlyfor those nearing higher risk levels. The study underscores the need forimmediate interventions to improve how students carry heavy schoolbags, especially for those experiencing ongoing musculoskeletal pain.Future research should focus on long-term impacts, ergonomicinterventions, and student perspectives to enhance school safety andhealth effectively across diverse student populations.